Buku pintar Indonesia - Sigar, Edi ([Jakarta?] : Delapratasa Pub., 2007)
Information on Indonesia.
Includes bibliographical references (page 498).
Keywords: Indonesia -- Miscellanea; Indonesia -- Civilization; Indonesia